Cardiovascular disease awareness among women with hypercholesterolemia and their health seeking behavior: A qualitative study - Samsudin, Suhaiza; Mohd Arifin, Siti Roshaidai; Md Aris, Mohd Aznan; Abdullah, Fa’iza (2019)
Cardiovascular diseases (CVD) are a group of disorders that affect the heart and blood vessels. It is an important cause of morbidity and mortality in Malaysian women. However, many women are not aware of it and have a misconception that CVD is a disease that only affects men. Therefore, the main objectives of this study are to explore CVD awareness among women who are at risk of developing the disease and evaluate their health seeking behaviour in regard to their hypercholesterolemia status. A series of in depth face-to-face interviews were conducted among 13 women who were found to have high cholesterol level detected in their blood during a routine medical screening at a primary health care clinic in the International Islamic University Malaysia, Kuantan, Pahang. All interviews were audio recorded and transcribed verbatim. NVIVO software Version 12 was used to code and manage all qualitative data. Results indicated that all participants had poor awareness of CVD. The majority of them did not perceive themselves as at high risk of developing CVD despite having high cholesterol levels in their blood. Poor CVD awareness, lack of knowledge and sociocultural aspect influenced their health seeking behaviour. This study provided an insight into the women’s awareness towards CVD. Health-care practitioners should elicit a patient’s awareness to facilitate the clinical management of CVD. Additionally, there is a clear need to increase CVD health awareness among women, especially those who are susceptible to CVD.